New Opportunities in the Diagnosis of the Implant-Associated Infection - Poliachenko, I.V.; Hrytsai, M.P.; Liutko, O.B.; Kolov, H.B.; Vitrak, K.V. (TERRA ORTHOPAEDICA, 2020)
Summary. Despite the improvement in the quality of implants, the number of complications in traumatology and orthopedics, which lead to infection, remains high. It is proved that untimely prescription of adequate antibiotic therapy for implant-associated infections can cause progression of the septic process until the development of shock and multiorgan failure and on practics leads to the development of resistance microorganisms to antibacterial drugs. An important point is to study the pathological microbial communities (bacterial film) in traumatology and orthopedics. All "classic" tests and markers of the infectious processhave low specificity and are not reliable enough for accurate diagnosis. These features are forced to development of additional microbiological diagnostics: the study of the destruction of the biofilm, which is removed from the implant surface with the help of ultrasound. The purpose of our study was to determine the effectiveness of the microbiological tests with sonication in patients with infectious process after osteosynthesis of long bones. Materials and Methods. Microbiological studies of the pathologically altered tissue biopsies directly at the implant and implant sonicates from the implant for osteosynthesis from 31 patients with chronic osteomyelitis or surgical site infection were performed. Results. As a result, the significant sonication efficiency was discovered: a 25.8% increase in positive results, 6.5% of E. aerogenes and E. faecalis cultures in association with S. aureus were isolated. Conclusions. Further improvement of the method and its application in specialized departments can give a positive diagnostic effect, which will subsequently improve the results of patient treatment.